Analisis Faktor Yang Mempengaruhi Minat Milenial Terhadap Boba vs Kopi di Kota Medan - Eva Christine Tinambunan; Arine Firyal Syahra; Nurmalatipah Hasibuan (Journal of Business and Economics Research (JBE), 2020)
Now culinary has become part of the lifestyle because the various foods and drinks that are considered interesting to taste. On this occasion the researcher limited the discussion by examining the factors that influenced millennial in choosing current drinks, namely coffee and bubble tea. The object of research is people who live in Medan, aged 17-25 years, and actively consume bubble tea or coffee. Some of the variables we use in researching are age, sex, occupation, choice of drinks and the reasons, price of drinks, the influence of people to the respondent's knowledge by consuming these drinks. The method used by researchers is a quantitative method that collecting the data by using a series of research instruments tests / questionnaires form of 39 people. The result, from 39 respondents, 26 of them chose bubble tea and 13 of them chose coffee as the preferred drink. In addition, the reason respondents liked one drink was because they liked the sweet taste as well as the quality of the drink. In consuming this drink, 64.1% of respondents bought drinks when they’re with their friends, followed by 15.4% of respondents who bought drinks when alone and with family. Finally, from a variety factors in choosing the drink 89% of respondents know the impact of consuming the drink they chose. This means the respondent's awareness in determining a choice for themselves is good enough.